Social Inclusion in Uruguay - Freire, German (World Bank, Washington, DC, 2020)
Uruguay is a regional leader in the path toward social inclusion. Sustained economic growth and redistributive policies have made it the most egalitarian country in Latin America. However, some groups are still excluded. Afro-descendants, persons with disabilities, women particularly in female-headed households and LGBTI people are more likely to be excluded. They face unequal opportunities, lower accumulation of human capital and skills, and a lack of voice and agency to have their points of views and aspirations of development included in decision making. This translates into disadvantages in education, health, housing, political representation, and employment, among others, and a higher tendency to live in poorer regions and slums. Excluded groups are also confronted with glass ceilings in the job market, which result in lower incomes and fewer opportunities. Uruguay has a robust matrix of social policies and one of the highest levels of public social spending in the region, but atomization of social programs and lack of coordination between them compromises their effectiveness. Closing the remaining gaps is possible and may not require large additional spending. Very often, changes in preexisting programs is all it takes to make them more socially inclusive. Policies that put social inclusion at their core do not necessarily do more, but they do things differently.